Rehabilitación visual sus tendencias y sus retos (2020)
Visual rehabilitation aims to make the most of the visual residual of patients and to develop skills that guarantee an increase in quality of life, and reduce limitations in daily activities, the risk of accidents, depression, social isolation. , among other health-related disorders. This led to an exhaustive search of bibliography about visual rehabilitation, the process of realization, and the aids that are emphasized to make the most of the vision that the patient has and that allows him to carry out activities.